Human metapneumovirus keeps dendritic cells from priming antigen-specific naive T cells - Céspedes, Pablo F (Blackwell Science Inc, 2013)
Human metapneumovirus (hMPV) is the second most common cause of acute lower respiratory tract infections in children, causing a significant public health burden worldwide. Given that hMPV can repeatedly infect the host without major antigenic changes, it has been suggested that hMPV may have evolved molecular mechanisms to impair host adaptive immunity and, more specifically, T-cell memory. Recent studies have shown that hMPV can interfere with superantigen-induced T-cell activation by infecting conventional dendritic cells (DCs). Here, we show that hMPV infects mouse DCs in a restricted manner and induces moderate maturation. Nonetheless, hMPV-infected DCs are rendered inefficient at activating naive antigen-specific CD4(+) T cells (OT-II), which not only display reduced proliferation, but also show a marked reduction in surface activation markers and interleukin-2 secretion. Decreased T-cell activation was not mediated by interference with DC–T-cell immunological synapse formation as recently described for the human respiratory syncytial virus (hRSV), but rather by soluble factors secreted by hMPV-infected DCs. These data suggest that although hMPV infection is restricted within DCs, it is sufficient to interfere with their capacity to activate naive T cells. Altogether, by interfering with DC function and productive priming of antigen-inexperienced T cells, hMPV could impair the generation of long-term immunity.